2006
DOI: 10.1093/rheumatology/kel278
|View full text |Cite
|
Sign up to set email alerts
|

Role of endothelin in chronic renal failure--developments in renal involvement

Abstract: Endothelin (ET)-1 is a potent vasoconstrictor with profibrotic and proinflammatory effects. Increasing evidence suggests that ET-1 and its cognate receptors are involved in a variety of progressive renal disorders, including diabetes, hypertension and glomerulonephritis. Several laboratory studies have demonstrated elevated expression of ET-1, which colocalizes with glomerular and tubulointerstitial injury, in addition to enhanced urinary excretion. Moreover, ET-1 expression correlates with disease severity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…ET-1 is involved in pulmonary hypertension (Zhang et al, 2005a(Zhang et al, , 2005b and cardiac failure (Wang et al, 2004) and upregulation of the ET pathway has been found in various renal disorders (Ohshiro et al, 2006;Richter, 2006;Dhaun et al, 2007). An over-activation of the ET A receptor subtype is consistent with findings in diabetic patients or animal models (Sugimoto et al, 2002).…”
Section: Discussionmentioning
confidence: 63%
“…ET-1 is involved in pulmonary hypertension (Zhang et al, 2005a(Zhang et al, , 2005b and cardiac failure (Wang et al, 2004) and upregulation of the ET pathway has been found in various renal disorders (Ohshiro et al, 2006;Richter, 2006;Dhaun et al, 2007). An over-activation of the ET A receptor subtype is consistent with findings in diabetic patients or animal models (Sugimoto et al, 2002).…”
Section: Discussionmentioning
confidence: 63%
“…These factors include endothelins, oxidative stressors, and inflammatory mediators. [24][25][26] Endothelins, such as ET-1, are vasoconstrictors that can also elicit inflammatory and fibrotic effects. 24 Oxidative stressors include reactive oxygen species, which promote vasoconstriction, the release of renin, and increased urinary protein excretion.…”
Section: Plasma Renin Activitymentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Furthermore, impaired kidney function might amplify the adverse effects on blood pressure that can be elicited by various prescription and over-the-counter medications, such as NSAIDs. 28 In this Review we address the necessity of frequent and accurate blood pressure monitoring in patients with CKD, the current recommendations regarding blood pressure target levels, and the rationale behind these recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, genetic variation in NOX4 might be associated with differential oxidative burden, thereby modulating diabetic nephropathy susceptibility. Endothelin-1, the predominant isoform in cardiovascular and renal systems, is the most powerful endogenous vasoconstrictor with profibrotic and proinflammatory effects [25]. It has been found to affect three pivotal aspects of renal physiology: (1) vascular and mesangial tone; (2) sodium and water excretion; and (3) cell proliferation and matrix formation [26].…”
Section: Discussionmentioning
confidence: 99%